(untitled)
Во македонската јазична територија постојат повеќе имиња на птици од редот на Strigiformes (bu, buf, buv, buh, buval, buhal, b’uhƒl, b’uh‚l, buhel, buarec, buo, b’uho, b’uhalo, bulut, bul’utin, b’ula ; ut, utka, ’utalen; lul’ejka, ulejka; d’umo;